Ectopic expression of the transcription factor CUC2 restricts growth by cell cycle inhibition in Arabidopsis leaves. (2nd January 2020) - Li, Xiaoyu; Zheng, Yucai; Xing, Qian; Ardiansyah, Rhomi; Zhou, Hui; Ali, Shahid; Jing, Tingting; Tian, Jingjing; Song, Xing Shun; Li, Yuhua; Müller-Xing, Ralf
ABSTRACT: Plant leaf margins produce small outgrowths or teeth causing serration in a regular arrangement, which is specified by auxin maxima. In Arabidopsis, the spatiotemporal pattern of auxin dependents on both, the transcription factor CUC2 and the signal peptide EPFL2, a ligand of the growth-promoting receptor kinase ERECTA (ER). Ectopic expression of CUC2 can have contrary effects on leaf growth. Ubiquitous expressed CUC2 suppresses growth in the whole leaf, whereas cuc2-1D mutants have enlarged leaves, through ER -dependent cell proliferation in the teeth. Here we investigated the growth dynamics of cuc2-1D leaves and the growth restricting the function of CUC2 using the ubiquitous inducible CUC2-GR transgene. In time courses, we dissected the serration promoting the function of CUC2 in the leaf margin and ectopic growth inhibition by CUC2 in the leaf plate. We found that CUC2 limits growth rather by cell cycle inhibition than by cell size control. Furthermore, endogenous CUC2 was rapidly induced by CUC2-GR indicating a possible auto-inducible feedback. In contrast, EPFL2 was quickly decreased by transient CUC2 induction but increased in cuc2-3 mutant leaves suggesting that CUC2 can also counteract the EPFL2-ER pathway. Therefore, tooth growth promotion and growth inhibition by CUC2 involve partially the same mechanism but in contrary ways.